OsBBX2 Delays Flowering by Repressing Hd3a Expression Under Long-Day Conditions in Rice - Yusi Yang; Jiaming Wei; Xiaojie Tian; Changhua Liu; Xiufeng Li; Qingyun Bu (Plants)
Members of the B-Box (BBX) family of proteins play crucial roles in the growth and development of rice. Here, we identified a rice BBX protein, Oryza sativa BBX2 (OsBBX2), which exhibits the highest expression in the root. The transcription of OsBBX2 follows a diurnal rhythm under photoperiodic conditions, peaking at dawn. Functional analysis revealed that OsBBX2 possesses transcriptional repression activity. The BBX2 was overexpressed in the rice japonica cultivar Longjing 11 (LJ11), in which Ghd7 and PRR37 were non-functional or exhibited weak functionality. The overexpression of OsBBX2 (OsBBX2 OE) resulted in a delayed heading date under a long-day (LD) condition, whereas the bbx2 mutant exhibited flowering patterns similar to the wild type (WT). Additionally, transcripts of Ehd1, Hd3a, and RFT1 were downregulated in the OsBBX2 OE lines under the LD condition. OsBBX2 interacted with Hd1 (BBX18), and the bbx2 hd1 double mutant displayed a late flowering phenotype comparable to that of hd1. Furthermore, OsBBX2 enhanced the transcriptional repression of Hd3a through its interaction with Hd1, as demonstrated in the protoplast-based assay. Taken together, these findings suggest that the OsBBX2 delays flowering by interacting with Hd1 and co-repressing Hd3a transcription.